Pendekatan Double Diamond untuk Meningkatkan Ketertarikan Pengguna pada Portal Akademik - Tri Sagirani; Gilang Ilham Septiawan; Mochammad Arifin (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
Wijaya Kusuma University is located in Surabaya. In 2012, Wijaya Kusuma University in Surabaya launched an academic portal website that gives students access to data about their needs for academic lectures. By sending questionnaires to 58 respondents who used the older edition of the User Experience Questionnaire, a problem request on the academic portal user experience was carried out in this study (UEQ). The old academic portal design scored well on the Attractiveness scale with a score of 0.83 (below average), Clarity with a score of 0.92 (below average), Efficiency with a score of 0.63 (below average), Accuracy with a score of 1.52 ( good), Stimulation with a score of -0.06 (poor), and Novelty with a score of 0.46. (Below Average). A maximum 200 word abstract in English in italics with Times New Roman 11 point. Abstract should be clear, descriptive, and should provide a brief overview of the problem studied. Abstract topics include reasons for the selection or the importance of research topics, research methods and a summary of the results. Abstract should end with a comment about the importance of the results or conclusions brief. By creating a new version of the academic portal design in the form of a user interface prototype based on UEQ results and user interviews, this research aims to enhance the user experience by making it likable, understandable, and familiar. The approach used in this study makes use of Double Diamond, which comprises four stages: Discover, Define, Develop, and Deliver. The test discussion's findings led to an evaluation of the new academic portal prototype design's key elements, including appealing appearance (Strongly Agree), layout effectiveness (Strongly Agree), easy-to-understand display (Strongly Agree), addition of clear information (Strongly Agree), color toughness (Strongly Agree), and front view (Strongly Agree). Thus, it can be said that the updated prototype design features a user interface that piques users' interest